Financial Capability Analysis in Central Kalimantan Province Before and After Regional Autonomy - David Antoni; Marhot Siregar; Sufridson Heno (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2018)
The purpose of this study was to determine the growth of local original income before and after regional autonomy, the elasticity of local original income before and after regional autonomy, share of regional original income before and after regional autonomy, and regional financial capacity index before and after regional autonomy. This study uses the Paired Sample t-Test analysis method which is a different paired sample test which is used only for the formulation of the problem regarding the Financial Capability Index before and after regional autonomy. The results of the study show that the regional financial capacity index consisting of growth in local revenues, elasticity of local revenue, and share of local revenue in 1999 and 2006 showed fluctuating differences. While based on the financial ability index value shows the average financial capability index of the 6 districts / cities of observation for 1999 and 2006, respectively 2.818 and 2,758 with standard devisions of 2382.82 and 348.28, respectively. The 1999 financial capability index also shows a higher variation compared to the value of the financial ability index in 2006. In addition, the growth of regional original income, local revenue elasticity before and after regional autonomy in 1999 and 2006 in 6 (six) parent districts shows elasticity fluctuating or insignificant. Share of local revenue before and after regional autonomy in 1999 and 2006 in 6 (six) main districts showed significant results. The financial ability index before and after regional autonomy in 1999 and 2006 showed fairly weak or insignificant results. This is due to the growth of local revenue, elasticity of local revenue, and fluctuating share of regional revenue and it does not appear that the increase occurs every year. Finally, for 6 (six) regencies / parent cities in Central Kalimantan Province their financial capacity is still low, so they need attention in terms of regional financial management and have an impact on improving the welfare of the community. These efforts can be carried out, among others, by building a performance-based system for compiling local revenues, as well as increasing human resources in the area of ??regional financial management.